PENGARUH LATIHAN PENDEKATAN TAKTIK TERHADAP KEMAPUAN DEFENSE PADA PESERTA EKSTRAKURIKULER FUTSAL PUTRA DI SMK AL JABBAR CILEDUG - Dede, Dede Yusuf Setiawan; Wahidi, Ribut; Muldan, Dadan (Journal of Physical Education and Sport Science, 2024)
This study aims to determine the effect of tactical approach training on the defense ability of male futsal extracurricular participants at SMK Al Jabbar Ciledug. This study uses quantitative methods. The research conducted is an experiment with the type of Pre-Experimental Designs. The research design used is one group pretest-posttest designs. The research sample amounted to 24 people. The data collection technique used observation, test, and documentation techniques. The research instruments were observation sheets, defense ability test sheets, and cameras. The data analysis technique consisted of pre-requisite analysis and hypothesis testing. The results showed that the defense ability of the male futsal participants of SMK Al Jabbar Ciledug before the application of the tactical approach was sufficient with an average value of 57. The defense ability of the male futsal participants of SMK Al Jabbar Ciledug after the application of the tactical approach was good with an average value of 80. There was an influence training on the tactical approach to defense abilities for male futsal extracurricular participants at SMK Al Jabbar Ciledug with a Sig. (2-tailed) 0.000.